The Theatre of the Occult Revival Alternative Spiritual Performance from 1875 to the Present - Lingan, E. (Palgrave Studies in Theatre and Performance History, 2014)
This book explores the religious foundations, political and social significance, and aesthetic aspects of the theatre created by the leaders of the Occult Revival. Lingan shows how theatre contributed to the fragmentation of Western religious culture and how contemporary theatre plays a part in the development of alternative, occult religions.